Enzyme assay for metal-reducing enzyme - Abd. Shukor, Mohd. Yunus; Syed, Mohd Arif; Shamaan, Nor Aripin; Ahmat Raslan, Shahrizal Rizwan (2009)

(untitled)
An improved enzyme assay system for screening potential molybdenum-reducing microbes from the environment for the purpose of bioremediation is described. Said method includes contacting said crude enzyme preparation from the organisms with either nicotinamide adenine dinucleotide reduced from (NADH) or nicotinamide adenine dinucleotide phosphate in reduced from (NADPH), as electron donor substrates and laboratory-prepared phosphomolybdate as the electron acceptor substrate. The resultant blue intensity is mesured colorimetrically using a spectrophotometer. Said laboratory-prepared phosphomolybdate comprises of a mixture of molybdate and phosphate in the ratio of 10 moles molybdate to 1 to 5 moles phosphate.